Kajian penambahbaikan kurikulum universiti Kuala Lumpur Malaysian Spanish Institute untuk memenuhi keperluan pelajar teknologi kejuruteraan industri automotif - Mohd Nizam Ab Rahman; Rahim Jamian (2008)
This case study focuses on the role of Universiti Kuala Lumpur Malaysian Spanish Institute (UniKL MSI) to produce technologist in order to reduce the shortage of skilled workers especially in the automotive industry. The purpose of the study therefore seeks to examine the effectiveness of Technical Education and Vocational Training (TEVT) curriculum of UniKL MSI to produce graduates that could immediately be productively employed by the automotive industry. The approach used in this study is through performance evaluation of students attending the Industrial Training Attachment (INTRA). The sample of study comprises of 37 students, 16 university supervisors and 26 industrial supervisors. The research methodology involves the use of quantitative and qualitative methods of data collections through the triangulation approach. The quantitative data was gathered from the students, university supervisors and industrial supervisors through the use of questionnaire. Meanwhile, the qualitative data was obtained from the students and university supervisors through the use of interview and observation. Both types of data have been processed and analyzed in order to summarize the results in terms of frequency and percentage by using the ‘Microsoft Office Excel 2003’. The result shows that industrial supervisors were satisfied with the students’ performance. Meanwhile, university supervisors rated moderate effectiveness of the UniKL MSI curriculum in producing graduates with appropriate skills and in meeting the industrial needs. During the period of study, several weaknesses in the curriculum have been identified for further continuous improvements. Recommendations and suggestions for curriculum improvement also include the enhancement of technical skills and competences of students towards fulfilling the needs of the automotive industries